The letters of Oscar Hammerstein II - Hammerstein, Oscar 1895-1960 (Oxford University Press, 2022)
Oscar Hammerstein II virtually invented the modern American musical, first with Show Boat and then in his celebrated collaborations with composer Richard Rodgers on Broadway classics like Oklahoma!, Carousel, and The King and I that continue to fascinate audiences today. A brilliant lyricist and playwright, Hammerstein innovated the American musical with his sophisticated storytelling that single-handedly elevated musical theater to a serious art form. But there were many more sides to Hammerstein: He was also a canny businessman, a successful producer, a mentor to Stephen Sondheim, and a social activist. This rich collection edited by Mark Eden Horowitz features hundreds of previously unpublished letters that show off all facets of Hammerstein's many engagements and his personality. Hammerstein's correspondence with major Broadway figures like Richard Rodgers, Stephen Sondheim, Jerome Kern, and Josh Logan tells the history of twentieth-century American show business while his exchanges with politicians and activists shed light on social issues of the period. What unites these letters across their vast range of themes is Hammerstein's compelling voice that reveals a man who was sharp, opinionated, and funny but also cared deeply about addressing the social ills that his musicals explored beyond the stage
Includes index
Keywords: Hammerstein, Oscar -- 1895-1960; Geschichte 1917-1960; Songwriter; Librettist; Musikproduzent; USA; Hammerstein, Oscar / II / 1895-1960 / Correspondence; Musical theater / United States / History / 20th century / Sources; Lyricists / United States / Correspondence; Hammerstein, Oscar / II / 1895-1960; Lyricists; Musical theater; United States; 1900-1999; History; Personal correspondence; Sources; Briefsammlung